A framework for integrated assessment of food production economics in South Asia under climate change. (January 2016) - Cai, Yiyong; Bandara, Jayatilleke S.; Newth, David
Abstract: Agriculture is a sector vulnerable to climate change. The potential decline of crop yields from this vulnerability has important policy implications for food security in South Asia. In this study an integrated assessment modelling framework is proposed to link a global economic model with global climate models via an econometric model of crop productivity. It is then used to examine the impact of climate change on food security in individual South Asian countries by exploring the interaction between climate-induced productivity change and changes in food production and food prices. The results of our simulations suggest that unfavourable climate change can reduce food production significantly from the historical trend and create upward pressure on food prices. This, in turn, will have serious adverse impacts on food security in the South Asian region. Highlights: We present an integrated model of food security in South Asia under climate change. We link a CGE model with climate models via an econometric model of crop yields. We explore interactions among climate change, food production and food prices. Climate change is expected to have serious impacts on food security in South Asia.